The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/5565956
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lavender and Citrus aurantium on Anxiety and Agitation of the Conscious Patients in Intensive Care Units: A Parallel Randomized Placebo-Controlled Trial

Abstract: Background. Conscious patients admitted to intensive care units (ICU) suffer from anxiety and agitation for various reasons, which can affect their recovery processes. Aims. To compare the effects of lavender and Citrus aurantium essential oils on anxiety and agitation of conscious patients admitted to ICUs. Design. A randomized parallel placebo-controlled trial. Methods. One hundred and fifty conscious patients admitted to ICUs were selected by convenience sampling and were randomly divided into three groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
4
0
4
Order By: Relevance
“…The results of a study showed that the interventions using music therapy and aromatherapy with chamomile-lavender essential oil could reduce the anxiety of nurses in clinical settings [ 69 ]. In 2021, the positive effects of lavender aromatherapy and Citrus aurantium aromatherapy on reducing the anxiety of patients were documented [ 70 ]. Inhalation with 1.5% lavender and chamomile essential oils for 30 nights decreased depression, anxiety, and stress levels in community-dwelling older adults [ 71 ].…”
Section: The Effects Of Lavender On Neurological/neuronal Disordersmentioning
confidence: 99%
“…The results of a study showed that the interventions using music therapy and aromatherapy with chamomile-lavender essential oil could reduce the anxiety of nurses in clinical settings [ 69 ]. In 2021, the positive effects of lavender aromatherapy and Citrus aurantium aromatherapy on reducing the anxiety of patients were documented [ 70 ]. Inhalation with 1.5% lavender and chamomile essential oils for 30 nights decreased depression, anxiety, and stress levels in community-dwelling older adults [ 71 ].…”
Section: The Effects Of Lavender On Neurological/neuronal Disordersmentioning
confidence: 99%
“…A análise dos óleos também demostrou resultados positivos em pacientes que tiveram seu quadro de ansiedade agravado durante o período da pandemia da Covid-19 (Lemos et al, 2022). Além disso, a redução da ansiedade e agitação em pacientes conscientes em Unidades de Terapia Intensiva (UTIs), também foi alcançada com o uso dos óleos essenciais de Lavanda e Citrus Aurantium (Karimzadeh et al, 2021).…”
Section: õZkaraman Et Al 2019unclassified
“…Ademais, esse tipo de intervenção frequentemente propicia o surgimento de inúmeras complicações de natureza física e psicológica, podendo induzir à dependência de substâncias psicoativas (Karimzadeh, et al,2021).…”
Section: Introductionunclassified
“…Citrus aurantium has been reported to alleviate anxiety and Bupleurum to alleviate depression. 26 , 27 In addition, Atractylodes macrocephala and Hawthorn display gastroprotective, anti-inflammatory, and digestive-promoting effects. 18 , 28 - 30 Clinical studies have also shown that ZZKZ is beneficial for DGBI including gastroesophageal reflux disease and postprandial distress syndrome (PDS).…”
Section: Introductionmentioning
confidence: 99%